2011
DOI: 10.1007/s10900-011-9411-5
|View full text |Cite
|
Sign up to set email alerts
|

HIV Among Military Personnel in the Niger Delta of Nigeria

Abstract: The military community is considered a high-risk environment for HIV transmission. In this study, a total of One hundred and fifty military personnel aged between 20 and 55 years attending the Nigerian army Hospital, Air Force Clinic and Police Clinic in the Niger Delta of Nigeria were randomly recruited for the study. Samples were tested for HIV using an immunochromatographic assay. The CD4 cell count was estimated using the Partec Cyflow Counter (Partec, Germany). Results of the study showed an overall HIV p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…In this study, we observed an overall sero-prevalence of 10.6%. This finding is consistent with previous report in other part of Niger Delta communities as reported by Azuonwu [3], with a prevalence of 15.0% [17]. The value obtained in this study is however much higher than the National sentinel sero-prevalence rate of 3.4%, this may probably be due to the sample size of the study or lack of knowledge about the mode of transmission and risk factors among the subjects, which includes high risk sexual behaviour, homosexual and hetero sexually promiscuity of some of the subjects living in the region.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In this study, we observed an overall sero-prevalence of 10.6%. This finding is consistent with previous report in other part of Niger Delta communities as reported by Azuonwu [3], with a prevalence of 15.0% [17]. The value obtained in this study is however much higher than the National sentinel sero-prevalence rate of 3.4%, this may probably be due to the sample size of the study or lack of knowledge about the mode of transmission and risk factors among the subjects, which includes high risk sexual behaviour, homosexual and hetero sexually promiscuity of some of the subjects living in the region.…”
Section: Discussionsupporting
confidence: 94%
“…This result is in corroboration with Azuonwu [3], finding, which reported that, there were twelve to thirteen HIV infected women for every infected man [3]. This fact may be due to casual attitude towards sex, tendencies towards multiple sex partners and risk behaviours (like sharing of sharp objects), that make them vulnerable to infection.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…They maintain modest levels of condom use and high rates of STIs, take advantage of modern medical treatment, and report good rates of partner notification when infected but low rates of notifying their spouses about infection episodes. A previous study by Azuonwu et al (Azuonwu et al, 2011) investigated the prevalence of HIV among a total of One hundred and fifty military personnel aged between 20 and 55 years in the Niger Delta of Nigeria and observed an overall HIV prevalence rate of 14.67%. The HIV prevalence among the male was higher than that of the female group (84% versus 16%).…”
Section: Hiv Infection and The Nigerian Militarymentioning
confidence: 99%